Pioneering 3D-printed dental crowns for adult patients: a pilot quasi-experimental study in Karachi, Pakistan - Sayani, Saleem; Faisal, Syed Shah; Asif, Nisha; Jabeen, Farah; Samnani, Saira; Asif, Osama; Ahmed, Hafiz Imtiaz; Muqeet, Abdul (Journal of the Pakistan Medical Association, 2026)
Objective: To compare patient-reported clinical outcomes between patients receiving three-dimensional-printed dental crowns versus conventional ones. Method: The pilot, quasi-experimental, single-blind study was conducted at Karachi Medical and Dental College, Karachi, from April to November 2024, and comprised patients with a clinical indication for dental crown placement. Based on the attending dentist’s clinical judgment, the participants were assigned to three-dimensional-printed crown group A or conventional crown group B. Data was collected using semi-structured interviews. Outcomes were assessed 15 days after the procedure, and intergroup comparison was done. Data was analysed using Stata 15. Results: Of the 24 participants, 12(50%) each were in the two groups, and both the groups had 6(50%) males and as many females. The mean age in group A was 29.8±8.4 years compared to 47.7±15.5 years in group B (p=0.002). Patients in group A reported more favourable outcomes, and higher satisfaction compared to those in group B (p<0.05). No significant difference was observed in occlusal function (p=0.478). Conclusion: The three-dimensional-printed dental crowns were found to be more effective than conventional crowns. Key Words: 3D-printed crowns, Digital dentistry, Conventional crown, Pilot study.